Laboratory and field studies on infochemicals of Brazilian noctuids - Araújo, Hernane Dias (2017)
Chemical compounds are mediators of various intra and interspecific interactions between insects, such as reproduction, pollination, food and host finding, predation and parasitism. Through the decoding of these channels of chemical communication over decades of research, it was possible to develop pest control techniques using behavior-modifying chemicals - the semiochem- icals. In this thesis, we evaluated an initial step in the research with semio- chemicals and the practical application in the field of a product already de- veloped through research focused on the control of noctuid moths. In the first study, we evaluated the calling behavior and sex pheromone production pat- tern of the invasive moth Helicoverpa armigera. It has been present in Brazil for a few years and caused great losses in di↵erent cultures. We observed that the production and emission of sex pheromone by females of a Brazilian popu- lation occurs generally at the end of the scotophase, di↵erent from that found in other populations and rarely seen in other moths. Helicoverpa armigera has a closely related species, the native moth Helicoverpa zea, and they have the same sex pheromone components. Therefore, the pattern found may help to elucidate a possible interaction between both species, since they can occur in the same place and at the same time. In the second study, we evaluated the efficiency of the plant-based attractant NOCTOVI R as an attract-and-viii kill method when mixed with 2% of the insecticide methomyl. The product proved to be efficient against Spodoptera frugiperda in corn crops, evidenced by the finding of dead moths in the areas treated with the attractant plus the insecticide. In addition, the density of males trapped in sex pheromone traps in the treated area was lower than in the area with no application. NOCTOVI R proved to be a promising product for the control of noctuid pest moths.